The effect of high-pressure torsion on irradiation hardening of Eurofer-97 - Strangward-Pryce, G; Song, K; Mizohata, K; Hofmann, F (Elsevier, 2023)
We investigate the effect of nano-structuring by high-pressure torsion (HPT) on the irradiation performance of Eurofer-97. Material was deformed to shear strains from 0 to ∼230, and then exposed to Fe3+ irradiation doses of 0.01 and 0.1 displacements-per-atom (dpa). Nanoindentation hardness increases monotonically with deformation, and with irradiation for the undeformed material. For both damage levels, less irradiation hardening is observed in severely deformed material. This effect is most prominent in the strain range ∼60 to ∼160, suggesting that nano-structuring may provide an approach for reducing irradiation hardening.